The Impact of Happiness at Work on Improving Job Performance: An Applied Study in Government Agencies in the Kingdom of Saudi Arabia 2025 - Al-Enzi, Khalid Awad (Journal of Humanities & Social Sciences, 2025)
The study aimed to explore the impact of workplace happiness on improving job performance in a governmental entity in Riyadh, Kingdom of Saudi Arabia. The research adopted the descriptive-analytical method due to its suitability for the topic. The problem of the study stems from the need to understand whether happiness at work can serve as a significant motivational factor influencing employees’ efficiency, productivity, and cooperation within the demanding environment of public institutions. Previous studies have focused mainly on private or educational sectors, leaving a research gap regarding public organizations in Saudi Arabia. Therefore, this study seeks to bridge that gap by investigating the extent to which workplace happiness affects job performance in government agencies. The importance of this study lies in highlighting the role of happiness as a key organizational factor that enhances productivity, strengthens employees’ commitment, and reduces absenteeism and turnover. Understanding how happiness contributes to performance improvement provides valuable insights for policymakers and human resource managers to design supportive environments that promote employee well-being and align with Vision 2030 objectives of improving workplace quality and efficiency in the public sector. The study is based on a sample of 384 employees and measures the independent variable of workplace happiness through three dimensions: participation, job satisfaction, and affective organizational commitment, while the dependent variable-job performance-includes teamwork, communication skills, and customer service. The main hypothesis states that workplace happiness has a statistically significant and positive effect on job performance. Sub-hypotheses propose that participation, job satisfaction, and affective commitment each have significant effects on improving performance. Findings are expected to show that higher levels of workplace happiness correspond with higher performance levels.